Effect of Fund Transfer, Revenue on Development Index as Moderation Variables - Sabda Alam; Binsar Hamonangan Simanjuntak (Journal of Business, Social and Technology, 2023)
One of the instruments to measure the level of success of a country in carrying out development is the human development index calculation approach. In essence, development is a change towards better conditions so that as a result of development activities it will have implications for the emergence of a budget and ultimately money is needed to realize development activities. During the twenty-four years of implementing fiscal decentralization in Indonesia, the number of transfers to the regions has increased significantly. However, efforts to increase regional revenues are often neglected, so that the goal of fiscal decentralization towards self-sufficient regional government funding has not been achieved to date. This study examines quantitatively how the influence of money arising from development activities, namely Central Government Transfer Funds and Regional Original Revenues, can generate benefits or whether the realization of the budget spent by local governments, namely Capital Expenditures, can generate a certain value or benefit for the community, so that in this study can be described through the human development index instrument. The sampling technique used in this study was purposive sampling. The data used in this study is secondary data obtained from the Central Bureau of Statistics and the Directorate General of State Financial Balance. The research method used is panel data regression with the Fixed Effect Model (FEM), where the data collected is cross-sectional data, namely 414 districts/cities in Indonesia for the period 2012 to 2020 which are time series data. The results obtained show that: (1) DTPP has a positive and significant effect on HDI; (2) PAD has a positive and significant effect on HDI; (3) Through capital expenditure mediation, DTPP has a negative and significant effect on HDI; and (4) Through the mediation of capital expenditure, PAD has a positive and significant effect on HDI..